Community awareness of dental fluorosis as a health risk associated with fluoride in improved groundwater sources in Mangochi District, Malawi. (10th February 2023) - Andreah, Kondwani; Tembo, Mavuto; Manda, Mtafu
Abstract: Fluoride is one of the priority chemicals being monitored under the sustainable development goal target for drinking water. Excessive ingestion of fluoride in concentrations higher than 1.5 mg/L may cause dental, skeletal and neurological disorders. The study assessed community awareness of dental fluorosis as a health risk associated with fluoride contamination in groundwater sources in Mangochi district. Water samples from 82 water points were tested for fluoride and concentrations between 0.2 and 27.2 mg/L were detected, with a mean value of 3.7 mg/L and a median value of 3.1 mg/L. Nine water points registered fluoride concentrations above 6 mg/L, which is Malawi standard value for fluoride in boreholes and shallow wells. Prevalence rate for dental fluorosis among children in the study was at 82.7%. However, 100% of the children's parents displayed low or no awareness of dental fluorosis as a health risk associated with fluoride contamination in drinking water. The study recommends the use of solar powered reticulated systems, whose water source shall be from a contamination-free zone, and supply to the affected villages. Human health risk assessment using the US-EPA approach needs to be conducted in the affected villages to understand the extent of exposure to fluoride-related health risks. HIGHLIGHTS: Fluoride in high concentrations was detected in some groundwater sources Dental fluorosis was evident in children Community awareness on the linkage between drinking water fluoride contamination and dental fluorosis was negligible The results imply ignorance of exposure to health risks related to drinking water fluoride